PENGARUH PROFITABILITAS, LEVERAGE, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN FOOD AND BEVERAGES - Hidayah, Norma; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The main objective of the company is to maximize the shareholder wealth, this can be achived bymaximizing firm value. But sometimes companies fail to increase their value, because one of the causative factorsis the company is less conscientious in applying the factor which can influence firm value. This research is aimedto find out and to prove empirically the influence of profitability, leverage and dividend policy to the firm value.The research sample has been selected by using purposive sampling. The data uses financial data food andbeverage companies in 2010-2014 periods have published their audited financial statements and have beenpresented in Rupiah currency consecutively. Based on these criteria then acquired 8 food and beveragescompanies with the observation period of 5 years (2010â2014). The result of this research shows that:profitability has positive influence to the firm value; leverage does not have any influence to the firm value anddividend policy does not have any influence to the firm value. Then the estimation result of regression shows thatthe predictive capability of these three independent variables to the firm value by 48% whereas the remaining52% is influenced by the other factors outside this research.Keywords: Profitability (ROA), Leverage (DER), Dividend policy (DPR), firm value (PBV).